A Pathophysiologically Hypertrophic 3T3-L1 Cell Model—An Alternative to Primary Cells Isolated from DIO Mice - Isabell Kaczmarek; Kristiana Schüßler; Andreas Lindhorst; Martin Gericke; Doreen Thor (Cells)
Adipocyte hypertrophy in individuals with obesity is connected to alterations in adipocyte function. These pathophysiological changes are studied using animal models and adipose tissue engineering. However, knockdown, overexpression, and stimulation studies would benefit from an easily applicable cell model. Although several models (free fatty acids, glucose restriction, and long-term incubation) have previously been described, our evaluation demonstrated that they lack important features described for hypertrophic adipocytes found in obesity. Therefore, we aimed to develop a cell model depicting the pathophysiological state of adipocytes in obesity by applying novel approaches (insulin, macrophage supernatant, and Tnfα) using 3T3-L1 cells. To analyze changes in adipocyte phenotype and function, we detected the cell size, lipid accumulation, insulin sensitivity, cytokine/adipokine secretion, and expression of lipolytic enzymes. Combining long-term incubation with insulin and Tnfα co-stimulation, we found significantly increased cell size and lipid accumulation compared to 3T3-L1 adipocytes differentiated with standard protocols. Furthermore, these adipocytes showed significantly reduced insulin sensitivity, adiponectin secretion, and lipolytic enzyme expression, accompanied by increased IL6 and leptin secretion. In summary, the described cell model depicts pathophysiologically hypertrophic 3T3-L1 adipocytes. This model can be used for knockdown, overexpression, and stimulation studies, thereby serving as an alternative to primary cells isolated from DIO mice.